DNA fingerprinting based assessment of adoption of improved maize varieties in Nigeria - CGIAR Research Program on Maize (2019)
We present key evidence on the adoption of improved maize varieties, using a DNA-fingerprinting approach to accurately identify the improvement status of the maize varieties grown by farmers Characterization of the most widely adopted improved varieties, in terms of area coverage, geographical distribution and age in Nigeria Linking improved variety identification with the structure of the maize seed system